Hereditary spastic paraplegia type 56: what a mouse can tell – a narrative review. Issue 2 (June 2022) - Parodi, Livia; Pujol, Claire
Abstract : Abstract: Hereditary spastic paraplegia type 56 (SPG56-HSP) is a rare autosomal recessive disorder caused by loss of function mutations in CYP2U1, leading to an early-onset limbs spasticity, often complicated by additional neurological or extra-neurological manifestations. Given its low prevalence, the molecular bases underlying SPG56-HSP are still poorly understood, and effective treatment options are still lacking. Recently, through the generation and characterization of the SPG56-HSP mouse model, we were able to take few important steps forward in expanding our knowledge of the molecular background underlying this complex disease. Leveraging the Cyp2u1 -/- mouse model we were able to identify several new diagnostics biomarkers (vitamin B2, coenzyme Q, neopterin, and interferon-alpha), as well as to highlight the key role played by the folate pathway in SPG56-HSP pathogenesis, providing a potential treatment option. In this review, we discuss the major role played by the Cyp2u1 -/- model in dissecting clinical and biological aspects of the disease, opening the way to a series of new research paths ranging from clinical trials, biomarker testing, and to the expansion of the underlying genetic and molecular, emphasizing how basic mouse model characterization could contribute to advance research in the context of rare disorders.